2023
DOI: 10.1021/acs.inorgchem.3c02696
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+ and Sb3+ Codoped Cs2ZnCl4 Metal Halide with Excitation-Wavelength-Dependent Emission for Fluorescence Anticounterfeiting

Tiancheng Zheng,
Huanxin Yang,
Yuling Liu
et al.

Abstract: In recent years, there has been a growing demand for luminescence anticounterfeiting materials that possess the properties of environmentally friendly, single-component, and multimode fluorescence. Among the materials explored, the low dimensional metal halides have gained wide attention because of unique characteristics including low toxicity, simple synthesis, good stability, and so on. Here, we synthesized Mn2+ and Sb3+ codoped Cs2ZnCl4 single crystals by a facile hydrothermal method. Under 365 nm excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…23,30,31 Cs 2 NaInCl 6 is a promising material that can be used in light-emitting applications due to its direct bandgap nature, but the parity-forbidden transition restriction makes undoped Cs 2 NaInCl 6 usually exhibit low PLQY. 17,21,32 Therefore, we used Sb 3+ -doped Cs 2 NaInCl 6 as the host and investigated the optical properties of Cs 2 NaIn 1− x Sb x Cl 6 crystals with different contents of Sb 3+ ions using steady-state PL and TRPL spectral measurements. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,30,31 Cs 2 NaInCl 6 is a promising material that can be used in light-emitting applications due to its direct bandgap nature, but the parity-forbidden transition restriction makes undoped Cs 2 NaInCl 6 usually exhibit low PLQY. 17,21,32 Therefore, we used Sb 3+ -doped Cs 2 NaInCl 6 as the host and investigated the optical properties of Cs 2 NaIn 1− x Sb x Cl 6 crystals with different contents of Sb 3+ ions using steady-state PL and TRPL spectral measurements. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ion doping has been proven to be an effective way to modulate the energy band structure and improve the optical properties of lead-free halide double perovskites. 16,18–22 For example, Zheng et al reported a dramatically improved PLQY of Cs 2 AgInCl 6 with co-doping of Bi 3+ and Na + ions. The introduction of the Bi 3+ ion can break the parity-forbidden transition and convert dark STEs into bright phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, time-resolved PL showed a single exponential decay behavior for both Mn 2+ and Sb 3+ emission. 77 Energy transfer between the dopants was observed for the Cs 2 NaInC l6 :RE 3+ ,Sb 3+ HDP. 78 Cs 2 NaInC l6 :Er 3+ ,Sb 3+ emits light in quite separated regions of the spectra – blue and near infrared.…”
Section: Hdp Photoluminescencementioning
confidence: 94%